2012
DOI: 10.1073/pnas.1211238109
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected nondenitrifier nitrous oxide reductase gene diversity and abundance in soils

Abstract: Agricultural and industrial practices more than doubled the intrinsic rate of terrestrial N fixation over the past century with drastic consequences, including increased atmospheric nitrous oxide (N 2 O) concentrations. N 2 O is a potent greenhouse gas and contributor to ozone layer destruction, and its release from fixed N is almost entirely controlled by microbial activities. Mitigation of N 2 O emissions to the atmosphere has been attributed exclusively to denitrifiers possessing NosZ, the enzyme system cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
554
4
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(574 citation statements)
references
References 58 publications
14
554
4
2
Order By: Relevance
“…Our data suggest that N 2 O accumulation is toxic to cellular metabolism at extracellular concentrations as low as ∼0.1 mmol/L. Thus, NosZ may play a previously unrecognized role in N 2 O resistance in microbial communities and this provides an insight into the function of NosZ in nondenitrifier bacterial genomes (35). The implications are that organisms that live in microbial communities and do not have B 12 -independent mechanisms, or NosZ, could be compromised by the release of N 2 O following incomplete denitrification by partial denitrifiers or during Cu-limitation.…”
Section: Discussionmentioning
confidence: 97%
“…Our data suggest that N 2 O accumulation is toxic to cellular metabolism at extracellular concentrations as low as ∼0.1 mmol/L. Thus, NosZ may play a previously unrecognized role in N 2 O resistance in microbial communities and this provides an insight into the function of NosZ in nondenitrifier bacterial genomes (35). The implications are that organisms that live in microbial communities and do not have B 12 -independent mechanisms, or NosZ, could be compromised by the release of N 2 O following incomplete denitrification by partial denitrifiers or during Cu-limitation.…”
Section: Discussionmentioning
confidence: 97%
“…Verrucomicrobia are known to be abundant in soils, but their ecological role remains unclear (37,38). The pathway's most abundant genus, Anaeromyxobacter (phylum Deltaproteobacteria), is common in agricultural soil and has recently been shown to carry out a previously unrecognized process of nondenitrifying N 2 O reduction to N 2 (39). The relative abundances of genera encoding the other six N pathways in the soil samples are reported in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, assigning function and taxonomy from short-read sequences is limited by genomic databases where annotations in some cases may be sparse and/or erroneous (56,57). The N cycle is an archetype of this problem, because new N processes and lineages continue to be identified (39,(58)(59)(60)(61). Despite these challenges, the application of metagenomic data to a trait-based framework offers a powerful avenue for elucidating the role that microbial communities play in regulating biogeochemical processes (24,62).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two recent studies revealed a physiological dichotomy in the diversity of N 2 O-reducing microorganisms (Sanford et al, 2012;Jones et al, 2013). These recent findings might also be of importance for understanding the relationship between N 2 O reduction and the activity and diversity of N 2 O-reducing microorganisms in biochar-amended soils and should be taken into account in future studies.…”
Section: Discussionmentioning
confidence: 99%